Changes in nail keratin observed by Raman spectroscopy after Nd:YAG laser treatment. Issue 4 (2nd August 2016) - Shin, Min Kyung; Kim, Tae In; Kim, Wan Sun; Park, Hun‐Kuk; Kim, Kyung Sook
Abstract: Lasers and photodynamic therapy have been considered a convergence treatment for onychomycosis, which is a fungal infection on the nail bed and nail plate. Laser therapies have shown satisfactory results without significant complications for onychomycosis; however, the mechanism of clearing remains unknown. In this work, we investigated changes in the chemical structure of nail keratin induced by Nd:YAG laser using Raman spectroscopy. Toe nails with onychomycosis were treated with 1064 nm Nd:YAG laser. After laser treatment, the disulfide band (490–590 cm −1 ) of nail keratin was rarely observed or was reduced in intensity. The amide I band (1500–1700 cm −1 ) also showed changes induced by the laser. The α‐helical (1652 cm −1 ) structures dominated the β‐sheet (1673 cm −1 ) in nontreated nail, but the opposite phenomenon was observed after laser treatment.